Pituicytoma, Spindle Cell Oncocytoma, and Granular Cell Tumor: Clarification and Meta-Analysis of the World Literature since 1893 - Covington, M.F.; Chin, S.S.; Osborn, A.G. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Pituicytoma, SCO, and GCT are poorly understood entities with confusing nomenclature and undetermined imaging characteristics. Our purpose was to confirm published cases of pituicytoma, SCO, and GCT with the newest 2007 World Health Organization criteria and elucidate imaging findings that distinguish these tumors from common entities such as pituitary adenoma. MATERIALS AND METHODS: A literature search identified 145 published cases (81 GCTs, 48 pituicytomas, and 16 SCOs). Case diagnoses were blindly reviewed by a neuropathologist according to the latest WHO criteria, resulting in 112 pathologically documented cases (64 GCTs, 35 pituicytomas, and 13 SCOs). Imaging illustrations from proved cases were reviewed to determine location, configuration, attenuation and signal intensity, and enhancement characteristics. RESULTS: Only pituicytomas presented as purely intrasellar lesions (7/33). Most GCTs were purely suprasellar (28/45). All SCOs were both intra- and suprasellar (13/13). Twenty-five percent of pituicytomas (6/22) and GCTs (7/30) appeared separate from the pituitary gland. All SCOs were infiltrating. Seventy-nine percent of entities appeared isointense to brain on T1-weighted image (34/43). Seventy-four percent of pituicytomas enhanced homogeneously (14/19). Twelve of 23 GCTs and 5/7 SCOs enhanced heterogeneously. Most GCTs were hyperattenuated to brain on CT (18/20). Eleven of 13 cases enhanced homogeneously. Visual disturbances were common symptoms for all entities (67/112). Diabetes insipidus was rare (4/112). CONCLUSIONS: Pituicytoma may be considered for purely intrasellar masses that are clearly separate from the pituitary gland. GCT should receive consideration for purely suprasellar lesions that are hyperattenuated to brain on CT. SCO should be considered for infiltrating pituitary masses with a mixed intra- and suprasellar location. A history of diabetes insipidus helps to exclude these tumors. DIdiabetes insipidusGCTgranular cell tumorSCOspindle cell oncocytoma